ANALISIS PENERAPAN PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV DI SDI DONGANG - Putri Hekto, Veronika Lukita; Divan, Stefanus; Ni, Laurentius (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of character education through Pancasila Education for fourth-grade students at Dongang Elementary School. The study used a qualitative, descriptive approach. Subjects included the principal, Pancasila Education teachers, and fourth-grade students. Data collection techniques included observation, interviews, and documentation. Data analysis involved data reduction, data display, preliminary onclusions, and final conclusions. The results indicate that the implementation of character education has not been effective. Character values ​​that have not been effective include religiousness, tolerance, honesty, and independence, while discipline and environmental stewardship have been effective. These findings demonstrate the crucial role of teachers in integrating character values ​​through learning and instilling them in daily classroom activities. Keywords: character education, Pancasila education, elementary school